Reaping Bananas in Trinidad - (:unkn) unknown (My University, 2009)
A picture of women carring bunches of bananas on their heads from the fields behind them. Description on the back of the postcard reads "Bananas were exported from Trinidad before the War. There are possibilities for the development of the industry". Postcard number B12.
Colour: Black and White; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Bananas--Trinidad and Tobago; Agriculture--Trinidad and Tobago; [1920]; Working class--Trinidad and Tobago; Men--Trinidad and Tobago; Women--Trinidad and Tobago; Clothing and dress--Trinidad and Tobago; Hats--Trinidad and Tobago; Headgear--Trinidad and Tobago; Harvesting--Trinidad and Tobago; Exports--Trinidad and Tobago; Banana trade--Trinidad and Tobago; Blacks--Trinidad and Tobago